Knowledge, Innovation and Agglomeration - regionalized multiple indicators and evidence from Brazil - Wilson Suzigan; Joao Furtado; Renato Garcia; Sergio Sampaio (European Regional Science Association (ERSA), 2005)
This paper develops multiple indicators to map the geographical distribution of knowledge and scientific and technological capabilities as proxies of the geographical distribution of Science, Technology & Innovation activities, and applies such indicators to data and information from the state of S\~ao Paulo, Brazil. The overall view of the geographical distribution of S,T&I activities in the state is complemented by the analysis of the same activities in the perspective of a local production and innovation system: the case of information and communication technologies in the micro-region of Campinas. The results show a pattern for the regional distributions of S,T&I activities along the main highways of the state, around metropolitan areas such as S\~ao Paulo and Campinas, and in regions where educational, science and technology, and R&D institutions are strongly concentrated. Firms tend to agglomerate in these areas and regions, forming local production and innovation systems. The paper produces evidence on the adherence of the geographical distribution of those systems to the geographical distribution of S,T&I activities as shown by the indicators. This confirms the empirical findings of the literature about the relationship between geography and innovation.
Keywords: 330